IDENTIFICATION OF ROOT (WILT) DISEASED COCONUT PALMS BEFORE VISUAL SYMPTOM EXPRESSION - V. Rajagoval; B. Sumathykuttyamma (International Coconut Community, 1989)
Determination of stomatal resistance (rs) and leaf water potential (ψ) were employed as techniques to distinguish coconut palms (Cocos nucifera L.) devoid of foliar symptoms ('apparently healthy') from those with symptorns of wilt disease viz. flaccidity, yellowing and necrosis ('wilt diseased'). Infected palms are characterized by low stomatal diffusive resistance and reduction in leaf water potential. Among the apparently healthy palms, some exhibited high rs and high ψ, characteristic of truly healthy palms, while others had the trend similar to the 'wilt' diseased palms. The latter group of palms was considered as disease 'suspects' and was closely monitored for the symptom expression. In about 10 to 14 months, all the palms 'suspected' to be diseased had the visual symptoms of the disease.